Effects of hydrophilic polymer-embedded membrane on permeability and cell adhesion during continuous hemofiltration - Kozue Kobayashi; Yoshitaka Kurihara; Shunichi Ueki; Kenichi Kokubo; Masaru Kubota; Hirosuke Kobayashi (Renal Replacement Therapy, 2022)
Abstract Background and Aims Clotting within the membrane and/or venous ‘air trap’ chamber is common problems during continuous blood purification therapy. Frequent clotting during continuous blood purification therapy leads to inadequate solute removal, an increased circuit and filter cost, and an increased burden for the medical staff. Improvements in filter membrane materials may reduce the extent of clotting and prolong the filter life. The purpose of the present study was to clarify the characteristics of an NV polymer-embedded membrane (NV-PS) after long-term use, especially the adhesiveness of blood cells and changes in the solute removal performance. Methods Continuous hemofiltration (CHF) experiments using a permeate recycle mode were performed for 24 h using the same porcine whole blood divided into two portions to compare the NV-PS with a conventional polysulfone membrane (PS). The activated clotting time was adjusted to within a range of 300–400 s. The change in the dextran sieving coefficient (SC) of the membrane and the residual blood clots in the filters were evaluated after the completion of the CHF experiment. Results The increase in the transmembrane pressure and the pressure drop of the hemofilter were significantly smaller using the NV-PS than with the PS. For larger molecules (SC $$ \leqq $$ ≦ 0.4), the reduction in SC after blood contact was significantly smaller for the NV-PS. Fewer blood cells remained in the residual blood clots when the NV-PS was used. Conclusion NV-PS has the advantages of showing a lower degree of reduction of the solute removal performance and also a lower degree of clogging of the hollow fibers during prolonged circulation. These characteristics may be expected to be advantageous when this membrane is used for continuous blood purification therapy in acute-phase patients.